2004
DOI: 10.1051/0004-6361:20040096
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the circumstellar gas in the Herbig Ae stars BF Orionis, SV Cephei, WW Vulpeculae and XY Persei

Abstract: Abstract. We present high resolution (λ/∆λ = 49 000)échelle spectra of the intermediate mass, pre-main sequence stars BF Ori, SV Cep, WW Wul and XY Per. The spectra cover the range 3800−5900 Å and monitor the stars on time scales of months and days. All spectra show a large number of Balmer and metallic lines with variable blueshifted and redshifted absorption features superimposed to the photospheric stellar spectra. Synthetic Kurucz models are used to estimate rotational velocities, effective temperatures an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…Many TACs observed are similar to those studied by Natta et al (2000) and Mora et al (2002Mora et al ( , 2004 in similar age Herbig Ae stars. These authors propose magnetospheric accretion of primordial gas as the most likely origin.…”
Section: Utrecht Echelle Spectrograph (Ues) On the William Herschelsupporting
confidence: 82%
“…Many TACs observed are similar to those studied by Natta et al (2000) and Mora et al (2002Mora et al ( , 2004 in similar age Herbig Ae stars. These authors propose magnetospheric accretion of primordial gas as the most likely origin.…”
Section: Utrecht Echelle Spectrograph (Ues) On the William Herschelsupporting
confidence: 82%
“…The differences between lines were consistent with the differences in density and temperature expected along one or more extended (∼0.1 AU) accretion columns or non-axisymmetric rotating/infalling structures (SA12). A similar approach, but using absorption lines, has been used to track cold matter moving around intermediate-mass stars (Mora et al 2002(Mora et al , 2004, and to trace the physical conditions along the accretion column in S CrA SE (Petrov et al 2014). With the time coverage we now have for EX Lupi in quiescence, we can explore the physical properties and also use the time variable to explore the dynamics of the accretion columns.…”
Section: Introductionmentioning
confidence: 99%
“…The spectroscopic monitoring of some sources (see e.g. Praderie et al 1986;Pogodin 1994;Rodgers et al 2002;Mora et al 2002Mora et al , 2004 revealed that the spectra of HAeBe objects are not only characterized by the presence of emission lines, but also by the complex variations observed in both the emission and absorption features. This variability is also characteristic of T-Tauri stars (see e.g.…”
Section: Introductionmentioning
confidence: 99%